Quality Evaluation of Herbal Yoghurt Produced Using Cinnamon (Cinnamon cassia), Garlic (Allium sativum) and Ginger (Zingiber officinale) - Ifeoma Elizabeth Mbaeyi-Nwaoha; Augustina Chinechendu Uzoigwe; Helen Onyeaka (Journal of Food Quality)
Yoghurt is a widely consumed fermented dairy product, known for its flavour and perceived health benefits. To create herbal yoghurt with unique attributes, different amounts (0, 4, 6 and 8 g) of cinnamon, garlic and ginger were incorporated into the yoghurt postfermentation, resulting in multiple samples. The research assessed various aspects of the herbal yoghurt, including proximate composition, micronutrients, physicochemical properties, antioxidant content, sensory attributes and microbiological characteristics. The proximate analysis revealed variations in moisture (86.67% to 87.79%), protein (4.26% to 4.28%), fat (3.82% to 3.91%), ash (0.88% to 0.95%) and carbohydrates (0.12% to 1.73%). The vitamin C content ranged from 0.21 mg/100 mg to 0.21 mg/100 mg, and vitamin A content from 2.79 IU to 2.86 IU. Phosphorus and calcium content varied from 90.43 mg/100 mg to 91.87 mg/100 mg and 53.72 mg/100 mg to 53.83 mg/100 mg, respectively. The herbal yoghurt exhibited a pH range of 4.57 to 4.67, total titratable acidity from 0.43 to 0.51 and IC50 for DPPH values from 20.83 to 21.78. In terms of sensory evaluation, the control sample (YCTRL) garnered the highest mean scores for all attributes, including appearance, aroma, taste, aftertaste, mouthfeel, consistency and overall acceptability. Panellists rated YGP1, which contained 4 g of ginger powder, as the herbal yoghurt with the most acceptability. Microbiological analysis indicated that the total viable count ranged from 7.9 × 102 (cfu/ml) to 1.1 × 103 (cfu/mL), with lactic acid bacteria counts varying from 1.4 × 103 (cfu/mL) to 2.3 × 103 (cfu/mL). Notably, no mould was detected in any of the yoghurt samples or the control, possibly due to the stringent aseptic conditions and hygienic measures maintained during production. From the results obtained, herbal yoghurt can serve as a highly nutritional functional food enriched with a variety of health benefits.